THE ROLE OF DEWAN MASJID INDONESIA OF DKI JAKARTA IN REVITALIZING MOSQUE FUNCTIONS IN THE MODERN ERA BASED ON THE PERSPECTIVE OF MAQASID SYARIAH - Al Hakim, Farrez; Maulidizen, Ahmad (Hukum Islam, 2024)
The burgeoning Muslim population in Indonesia has led to the construction of numerous mosques, yet their proliferation hasn’t significantly impacted community welfare as expected. Dewan Masjid Indonesia, established to foster mosques as centers for worship, community development, and unity, seeks to revitalize their role in modern society. This research delves into the strategies employed by Dewan Masjid Indonesia of DKI Jakarta to achieve this objective. Employing a qualitative descriptive approach, the study utilizes primary data collection methods such as observation, interviews, and documentation, supplemented by a review of existing literature. Data analysis follows Miles and Huberman’s model, involving data reduction, presentation, and conclusion drawing. Findings reveal the implementation of various programs aimed at mosque revitalization, though significant impact remains elusive due to the nascent stage of these initiatives. Recommendations include the recruitment of competent, young members to strategic positions within the council and prioritizing budget allocation towards digital data management and security. By addressing these areas, the council can enhance its effectiveness in revitalizing mosque functions and better meet the evolving needs of the Muslim community in Jakarta. This research contributes to the understanding of mosque management strategies in contemporary Indonesia and provides insights for enhancing the role of mosques in societal development